The Prevalence and Characteristics of Shoulder Pain in Female Patients with Coronary Artery Bypass Graft (CABG) - Shiva Mousavi; Behnoosh Vasaghi-Gharamaleki; Jalil Mirza-Mohammad Khanpour; Tahereh Khosravian-Arab (Shiraz University of Medical Sciences, 2017)
Background: Currently, cardiovascular disease is the most common cause of death in the world. The current study aimed to determine the prevalence and characteristics of shoulder pain in female patients with coronary artery bypass graft (CABG). Methods: This cross-sectional study enrolled 136 women after (CABG) through easy access, and questionnaires were distributed to them. The subjects were asked to complete the questionnaire regarding the time of incidence and characteristics of their shoulder pain, their history of exercise, and their history of pulmonary, cardiovascular, and other diseases. The patients' intensity of pain was measured using the visual analog scale (VAS). Results: In this study, 45 patients had shoulder pain. In nearly half of the patients, the pain began from the left shoulder, and one-third of the patients had pain in both shoulders. Onset of pain was sudden in more than 50% of cases. Conclusion: One-third of patients who underwent CABG suffered from shoulder pain which appeared quickly and within less than a day. The pain was frequently in the left shoulder or between the shoulder areas. Since the age of patients in this study was 50+ years, if the pain persisted, the probability of incidence of frozen shoulder is high.